Perioperative Management of a Patient Taking Suboxone® at the Time of Ambulatory Surgery - Shawn H. Malan; Christopher H. Bailey; Narjeet Khurmi (Case Reports in Anesthesiology)
In 2016, more than 11 million people reported misuse of opioids in the previous year. In an effort to combat opioid use disorder (OUD), the use of agonist/antagonist is becoming increasingly common, with more than 2.2 million patients reporting use of a buprenorphine containing medication such as Suboxone®. Buprenorphine is a unique opioid which acts as a partial μ agonist and ĸ antagonist. These properties make it an effective tool in treating OUD and abuse. However, despite its advantages in treating OUD and abuse, buprenorphine can make it difficult to control acute perioperative pain. We present a case in which the Mayo Clinic Arizona protocol for patients undergoing minimally invasive ambulatory surgery while taking Suboxone® is successfully executed, resulting in adequate postoperative pain control and timely discharge from the postanesthesia recovery unit.